2022
DOI: 10.1002/adma.202207198
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Nano‐Optogenetic Activation of Cancer Immunotherapy via Engineered Bacteria

Abstract: Certain obligate and facultative anaerobic microbes preferentially grow within this region, [2,3] which makes them ideal platforms for delivering antitumor therapeutics. [4,5] Different from conventional nano-drug delivery systems, bacteria-based drug carriers can be designed to generate and release drugs, which avoids the need for cumbersome post-purification or delivery protection. [6] However, bacteria sometimes can grow outside their natural niches, leading to offtarget therapeutics release that may incur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…For example, certain species of Escherichia coli (E. coli) exhibit the capability to sense blue light and release the encoded flagellin B. Leveraging these properties, a bacteria-based biohybrid was constructed with E. coli and lanthanide UCNPs for optogenetic cancer immunotherapy. [64] In addition, an "immune guide" based on magnetite nanoparticles was developed to recruit and activate macrophages for enhanced immunotherapies. [62] Alternatively, the nanostructures can be enclosed by the membranes derived from cells to form a biohybrid system.…”
Section: Biohybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, certain species of Escherichia coli (E. coli) exhibit the capability to sense blue light and release the encoded flagellin B. Leveraging these properties, a bacteria-based biohybrid was constructed with E. coli and lanthanide UCNPs for optogenetic cancer immunotherapy. [64] In addition, an "immune guide" based on magnetite nanoparticles was developed to recruit and activate macrophages for enhanced immunotherapies. [62] Alternatively, the nanostructures can be enclosed by the membranes derived from cells to form a biohybrid system.…”
Section: Biohybridsmentioning
confidence: 99%
“…Emission of light at shorter wavelengths than incident lights without blinking Photodynamic therapy and optical tracking [42] Gd-doped Au nanoparticles Magnetic activity and optical responsiveness Contrast agents for multi-modal imaging and imageguided therapy [43] Gd-doped CuS nanoparticles Magnetic activity and optical absorption Contrast agents for multi-modal imaging; localized hyperthermia; and image-guided therapy [44] Cu nanoparticles Radioactivity for 64 Cu Probe for positron emission tomography (PET) [45,46] Graphene and graphene oxide (GO) Flexibility and structural reinforcement; catalytic activity; and conductivity Drug delivery and tissue repair or regeneration [47] Iron manganese silicate nanoparticles (IMSN)…”
Section: Strong Optical Absorption For Photothermal Heating and Catal...mentioning
confidence: 99%
“…This work provided an NIR‐photoactivable hybrid bacteria systems based on optogenetics for tumor immunotherapy. [ 101 ] Other than light‐induced control elements, temperature‐based transcriptional regulators can be an alternative strategy for spatiotemporal control. Among them, some emerging studies have demonstrated that focused ultrasound can generate thermal bioswitches to control the expression of bacterial gene by constructing a temperature‐actuated therapeutic circuit.…”
Section: Biomedical Applications Of Hybrid Bacteria Systemsmentioning
confidence: 99%
“…Public opinion about GMOs is often divided, with concerns about their safety, ethics, and potential environmental impact contributing to skepticism and resistance. [167][168][169][170] In light of this, fostering public trust and acceptance is critical for the successful implementation of GEB applications in healthcare. This can be achieved through transparent communication about the benefits and risks of GEB, as well as the measures taken to ensure their safety.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%